c-MYC Levels and Metabolic Parameters in Triple-Positive and Triple-Negative Breast Cancer - Doaa N. Abood; Perry H. Saifallah (Diyala Journal of Medicine, 2025)
Background: Breast cancer is a complex, heterogeneous disease and the most common malignancy among women. It is classified based on the presence of estrogen receptors (ER), progesterone receptors (PR), and HER2. Rapid proliferation of cancer cells increases their energy demands leading to enhanced glycolysis and lactate accumulation. Lactate dehydrogenase (LDH) is pivotal in this process, particularly in tumors with anaerobic metabolism. The transcription factor c-Myc (cellular myelocytomatosis oncogene) promotes aerobic glycolysis by increasing glucose uptake and lactate production are a hallmark of the Warburg effect. Objectives: This study was aimed to evaluate c-Myc expression levels in patients with triple-positive breast cancer (TPBC) and triple-negative breast cancer (TNBC), comparing them to healthy control. Patients and Methods: The study included 80 women (ages 35–66): 20 with TNBC, 20 with TPBC, and 40 individual healthy as a control, matched for age, sex, and Body Mass Index (BMI). Serum levels of c-Myc, CA 27-29 was measured using an ELISA sandwich technique. Additionally, lactate dehydrogenase (LDH), glycated hemoglobin (HbA1c), liver enzymes (ALT and AST), and lipid profiles were assessed using spectrophotometric techniques. Results: c-Myc levels were significantly higher in breast cancer patients (4.71 ± 3.75 ng/ml) compared to controls (0.81 ± 0.44 ng/ml, p = 0.001). LDH and CA 27-29 levels were significantly elevated (p = 0.001). Metabolic parameters, including HbA1c%, ALT, AST, and lipid profiles (except HDL), showed significant changes, with reduced HDL levels in cancer patients. Notably, TNBC patients exhibited higher c-MYC and HbA1c levels compared to TPBC patients. Conclusion: Elevated c-Myc levels are associated with metabolic reprogramming in breast cancer and may serve as a potential therapeutic target. The higher c-Myc expression in TNBC correlates with its more aggressive nature, suggesting c-Myc's role in tumor progression. Keywords: Breast cancer, c-Myc, Lactate dehydrogenase, Triple-negative breast cancers, Triple-positive breast cancer.